Computerized tomography compared with radiography in the diagnosis of lateral trochlear ridge talar osteochondritis dissecans in dogs - Gielen, I.; van Ryssen, B.; van Bree, H. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
In this retrospective study, we compared the value of radiographic and computerized tomographic (CT) imaging for the diagnosis of lateral trochlear ridge talar osteochondritis dissecans (LTRT-OCD) in 11 tarsocrural joints. The flexed dorsoplantar skyline and the plantarolateral-dorsomedial projections were the most reliable for radiographic detection of OCD fragments (in 7 of the 11 joints). Overall, radiography detected OCD fragments in 8 of 11 joints. By contrast, the OCD fragments could be visualized and exactly localized by CT in all 11 joints. Computerized tomography allowed the talar ridges to be inspected without superimposition of any bony structures. This information may be very useful when minimal invasive techniques are used to treat LTRT-OCD lesions. The findings of this study suggest that CT is superior to radiography for making a diagnosis of LTRT-OCD in the dog.
Keywords: Dog; computerized tomography; osteochondritis dissecans; talus